Analisis Pesan Visual Bahaya Virus Covid-19 Dalam Film Animasi “ Larva” - Hasbullah Hasbullah; Andi Sofyan Anas; Anak Agung Gde Agung Indrawan; Tomi Tri Sujaka (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
The COVID-19 pandemic has paralyzed all activities and economies in almost all land areas of the world. The paralysis of community activities in various places disturbs creative ideas emerging through visual communication media, one of which is the animation of Larva from South Korea. The problem to be raised in this paper is about how the form of visual messages conveyed through Larva animation. The purpose of this article is for the audience to understand the message that is hidden behind the Larva animation. The method used in this paper is qualitative with observation data collection techniques or direct observation of Larva animation videos and literature study. Data analysis techniques, namely, reduction, presentation, and drawing conclusions based on the semiotic theory of Raland Barthes. The results presented in this paper lead to a visual message that displays the shape at the denotative level of the covid-19 virus in red to purple plus the effect of a dirty brown color that attacks larvae that are eating without implementing health protocols so that the Larva cough and spread the virus a group of larvae. which is enjoying food and immediately dies, then attacks the two red and yellow Larva. However, they apply health protocols such as washing hands using hand sanitizer and wearing masks. Connotatively, this visual message illustrates the importance of implementing health protocols during this COVID-19 period.